Chilo suppressalis heat shock proteins are regulated by heat shock factor 1 during heat stress. Issue 1 (1st November 2022) - Dong, Chuan‐Lei; Feng, Zhu; Lu, Ming‐Xing; Du, Yu‐Zhou
Abstract: Heat shock factor 1 (HSF1) functions to maintain cellular and organismal homeostasis by regulating the expression of target genes, including those encoding heat shock proteins (HSPs). In the present study, the gene encoding HSF1 was cloned from the rice pest Chilo suppressalis, and designated Cshsf1 . The deduced protein product, Cs HSF1, contained conserved domains typical of the HSF1 family, including a DNA‐binding domain, two hydrophobic heptad repeat domains, and a C‐terminal transactivation domain. Real‐time quantitative PCR showed that Cshsf1 was highly expressed in hemocytes. Expression analysis in different developmental stages of C. suppressalis revealed that Cshsf1 was most highly expressed in male adults. RNAi‐mediated silencing of Cshsf1 expression reduced C. suppressalis survival at high temperatures. To investigate the regulatory interactions between Cshsf1 and Cshsps, the promoters and expression patterns of 18 identified Cshsps in C. suppressalis were analysed; four types of heat shock elements (HSEs) were identified in promoter regions including canonical, tail–tail, head–head, and step/gap. The expression of Cshsp19.0, Cshsp21.7B, Cshsp60, Cshsp70 and Cshsp90 was positively regulated by Cshsf1 ; however, Cshsp22.8, Cshsp702, Cshsp705 and Cshsp706 gene expression was not altered. This study provides a foundation for future studies of HSF1 in insects during thermal stress. Abstract : Cshsf1 is sensitive to high and low‐temperature stress from Chilo suppressalis, with maximal expression at 39 and 0°C after 2 h. When Cshsf1 was silenced, Chilo suppressalis larvae exhibited a lower rate of survival at 39°C compared to the treatments at 27°C. Cshsf1 directly or indirectly regulates the expression of 18 Cshsps in Chilo suppressalis.